Translation of Terms of Address from English into Persian: Strategies in Focus - Lotfollahi, Bahareh; Dabbaghi, Azizollah (Richtmann Publishing, 2012)
This paper investigates the kind of translation strategies and procedures used by translators in the translation of terms ofaddress from English into Persian in three short stories,